Breakdown voltage enhancement of gate field plate Al0.295Ga0.705N/GaN HEMTs. Issue 8 (3rd August 2021) - Murugapandiyan, P; Hasan, Md. Tanvir; Rajya Lakshmi, V; Wasim, Mohd; Ajayan, J; Ramkumar, N; Nirmal, D
ABSTRACT: The breakdown characteristics of Al0.295 Ga0.705 N/GaN high electron mobility transistors (HEMTs) have been studied with Al0.04 Ga0.96 N blocking layer and gate field plate technique. LG = 0.4 µm HEMT with 0.8 µm SiN passivation shows 2.16 A/mm drain current (IDSmax ) at gate voltage, VGS = 2 V. The breakdown voltage of the HEMT is investigated for various field plate length (LFP = 1, 1.25, 1.5, 1.75, and 2 µm) and the device shows the maximum VBR of 871 V and JFoM of 34.88 THz-V for a gate-field plate length (LFP ) = 1.75 µm. The device performance has also been studied for the high-k passivation HfO2 layer with an identical structure. The device shows an enhanced VBR of 912 V with JFoM of 25.53 THz-V. These results indicate that the proposed Al0.295 Ga0.705 N/GaN/Al0.04 Ga0.96 N double heterojunction (DH) HEMTs are suitable devices for next-generation high-power microwave applications.